A manualização do saber linguístico: o discurso sobre igualdade em manuais de linguagem inclusiva de gênero do Brasil - Cruz, Camilla Machado (2023)
This study presents a discursive analysis, based on the French Discourse Analysis (DA), articulated to the History of Linguistic Ideas (HIL), of two Brazilian genderinclusive language manuals, digitally published, authored by relevant political and governmental institutions. Political representation in Brazil: Tribunal Superior Eleitoral (TSE) and Simulação das Nações Unidas para Secundaristas (SINUS). The manuals analyzed are the following: “Manual de linguagem inclusiva (SINUS, 2017) and Guia de linguagem inclusiva para flexão de gênero: aplicação e uso com foco em comunicação social (TSE, 2021). The objective of this research is to understand how the process of manualization of linguistic knowledge occurs in Brazilian inclusive language manuals, through an analysis based on the theoretical-methodological apparatus of DA, mobilizing concepts such as: discourse, language, discursive formation, ideological formation (PÊCHEUX, 2014a) and digital discourse (DIAS, 2015). According to HIL, we understand the manual as a linguistic-technological instrument (AUROUX, 2014), as well as part of the manualization process (PUECH, 1998). We need to go beyond DA and HIL to carry out these analyses, since it is essential to be based on the concept of performative gender (BUTLER, 2015). We emphasize that this discursive analysis is established in three moments. First, we list Brazilian gender-inclusive language manuals, chosen for being current, concise and freely available on the internet. In a second moment, to elaborate the research corpus, we chose two manuals. In a third moment, we analyzed, according to the analytical steps proposed by Orlandi (2020a). It is worth mentioning that the discursive analysis was carried out thinking about the production of meanings conforming to Pecheutian theory, permeating the relationship between the subject, language, ideology and history. That said, from our interpretation gestures, the analyzed discursive sequences present discourses that produce meanings about equality in socio-historically determined institutions. We reiterate that we seek to understand how the senses are organized, in a process of manualization, through an analysis of the discourse on equality, considering the emergence of the publication of inclusive language manuals in Brazil, from the beginning of the second decade of the 21st century, an event which symbolizes a potential scientific production of Linguistics, to the fields of knowledge of AD and HIL.